Invariant natural killer T cells in lupus patients promote IgG and IgG autoantibody production. Issue 2 (27th November 2014) - Shen, Lei; Zhang, Hong; Caimol, Maria; Benike, Claudia J.; Chakravarty, Eliza F.; Strober, Samuel; Engleman, Edgar G.
<x xml:space="preserve">Abstract</x> IgG autoantibodies, including antibodies to double‐stranded DNA (dsDNA), are pathogenic in systemic lupus erythematosus (SLE), but the mechanisms controlling their production are not understood. To assess the role of invariant natural killer T (iNKT) cells in this process, we studied 44 lupus patients. We took advantage of the propensity of PBMCs from patients with active disease to spontaneously secrete IgG in vitro. Despite the rarity of iNKT cells in lupus blood (0.002–0.05% of CD3‐positive T cells), antibody blockade of the conserved iNKT TCR or its ligand, CD1d, or selective depletion of iNKT cells, inhibited spontaneous secretion of total IgG and anti‐dsDNA IgG by lupus PBMCs. Addition of anti‐iNKT or anti‐CD1d antibody to PBMC cultures also reduced the frequency of plasma cells, suggesting that lupus iNKT cells induce B‐cell maturation. Like fresh iNKT cells, expanded iNKT‐cell lines from lupus patients, but not healthy subjects, induced autologous B cells to secrete antibodies, including IgG anti‐dsDNA. This activity was inhibited by anti‐CD40L antibody, as well as anti‐CD1d antibody, confirming a role for CD40L‐CD40 and TCR‐CD1d interactions in lupus iNKT‐cell‐mediated help. These results reveal a critical role for iNKT cells in B‐cell maturation and autoantibody production in patients with lupus.